MAIN‐LIKE1 is a crucial factor for correct cell division and differentiation in Arabidopsis thaliana. (12th March 2014) - Ühlken, Christine; Horvath, Beatrix; Stadler, Ruth; Sauer, Norbert; Weingartner, Magdalena
Summary Plant development requires accurate coordination of gene expression, both in actively dividing meristematic cells and differentiated cells. Cell fate establishment and maintenance, among others, are mediated by chromatin organization complexes that determine the stable transcriptional states of specific cell types. Here, we focus on MAIN‐LIKE1 (MAIL1), one of three homologs of MAINTENANCE OF MERISTEMS (MAIN), which form a plant‐specific gene family in Arabidopsis thaliana. We show that MAIL1 encodes a ubiquitously expressed nuclear protein. A mail1 loss‐of‐function mutant developed short primary roots, in which the meristematic cells accumulated DNA double‐strand breaks and underwent massive cell death. In addition, mail1 mutant showed also cell differentiation defects in root and shoot tissues, and developed disorganized callus‐like structures. The genetic interaction between main and mail1 mutants suggests that they act in the same pathway, and that both are essential for maintaining correct cell division acitivity in meristematic cells, while MAIL1 has an additional function in differentiating cells.